Dynamiques interculturelles en milieu de travail et associatif : des enjeux incontournables pour une participation démocratique des néo-Québécois - Jorge Frozzini; Audrey Gonin; Marie-Josée Lorrain (Communiquer)
The workplace is one of the main intercultural meeting places where learning and adaptation to the new social environment develop and influence democratic life. However, there is little research linking employment issues to the democratic participation of migrants and immigrants. Using data from three parallel studies and drawing on the 3D model (diversity, discrimination and dialogue) developed by White (2017 and 2018), we conduct a meta-analysis around questions about difficulties met in accessing employment and having good working conditions, and the strategies (pathways) adopted to initiate intercultural dialogue. This analysis makes it possible to grasp some strategies allowing the transition from a situation of discrimination and non-recognition of diversity to one of dialogue that supports citizen participation. This article highlights that the fight against discrimination, far from being opposed to dialogue, is a way to establish it, with a view to reducing existing gaps between neo-Quebecers and members of the host society. The analysis shows that some of these strategies require significant investment in sectors that are more open to New Quebecers. These strategies take a variety of forms that also allow recognition of some of their skills.